Prurigo: review of its pathogenesis, diagnosis, and treatment - Criado, Paulo Ricardo; Ianhez, Mayra; Criado, Roberta Fachini Jardim; Nakano, Juliana; Lorenzini, Daniel; Miot, Hélio Amante [UNESP] (Elsevier, 2024)
Prurigo is a reactive, hyperplastic skin condition characterized by pruritic papules, plaques, and/or nodules. The temporal classification includes acute/subacute and chronic disease (≥ 6 weeks), with different clinical variants, synonymies, and underlying etiological factors. The immunology of chronic prurigo shows similarities with atopic dermatitis due to the involvement of IL-4 and IL-13, IL-22, and IL-31. Treatment includes antihistamines, topical steroids, dupilumab, and JAK inhibitors. Several conditions manifest clinically as prurigo-like lesions, and the correct clinical diagnosis must precede correct treatment. Furthermore, chronic prurigos represent a recalcitrant and distressing dermatosis, and at least 50% of these patients have atopic diathesis, the treatment of which may induce adverse effects, especially in the elderly. The quality of life is significantly compromised, and topical treatments are often unable to control symptoms and skin lesions. Systemic immunosuppressants, immunobiologicals, and JAK inhibitors, despite the cost and potential adverse effects, may be necessary to achieve clinical improvement and quality of life. This manuscript reviews the main types of prurigo, associated diseases, their immunological bases, diagnosis, and treatment.
Keywords: Dermatitis, atopic; Drug therapy; Immunocompromised host; Janus kinase inhibitors; Prurigo; Pruritus